Ken Bugul’s Language: Its Formation and Characteristics - Sacharewicz, Edyta (Literatūra, 2023)
The aim of this article is to analyse Ken Bugul’s written language and its specificities. This Senegalese writer, like most French-speaking authors, has had to define her own written language, which becomes a mixture of French, the language of the coloniser, and Wolof, her mother tongue. The author of this article also draws attention to three experiences in Bugul’s personal life that have influenced her literary language, called by Christian Ahihou “la langue bugulienne”.
Keywords: Ken Bugul; language of writing; french; wolof